The use of Malaysian penal code in combating internet theft / Azlan Abdul Roni Hasan and Siti Kharolina Baharuddin - Hasan, Azlan Abdul Roni; Baharuddin, Siti Kharolina (Faculty of Law, 2005)
Our research encompasses the study of whether it is advisable to modify the definition of theft in the Penal Code to include non-corporeal things, in order to make it available to be used in prosecuting internet theft. The purpose of study is to find out whether there really is a need to amend the word "property" in the Penal Code to extend it into the realm of cyberspace or whether there are already sufficient Acts that deals with the Information Technology crimes. We choose this subject as to the adequacy of the Penal Code because we find that the essence of internet theft in the cyberspace and the elements of theft in the Penal Code to be coincide. In order to discover the level of efficiency of the Code, we used the method of library research, internet research, and consultation. We found out that, the internet theft situation in Malaysia is not as bleak as the situation in the US. Thus, the existing cyber statutes enacted is sufficient to deals with internet theft, although the strength of these statutes is unknown since the judicial organs seems incline to use it. In conclusion, we found that the internet theft in Malaysia, although not at an alarming rate, should be curb before serious damage can be done, and the cyber statutes should be put to test to determine its vulnerability.